Efeitos de vários teores de energia e proteína sobre o desempenho de frangos de corte e composição da carcaça - Islabão, Narciso; Brandão Fonseca, José; Campos, Joaquim; da Silva, Dirceu Jorge (Revista Ceres, 2025)
The effect of four levels of energy (2800, 2900, 3000 and 3100 Kcal of ME/kg of ration) and four levels of protein (18, 20, 22 and 24%) was studied over a period of four weeks, using day old chicks. The ration consisted of two basic parts, the first making up 95% of the total ration and the second 5%. The first part consisted of ground corn, soybean meal, wheat Shorts and soybean oil, the quantity of each being adjusted to give the desired levels of energy and protein. The second part of the ration was a pre-mix consisting of vitamins, minerals, coccidiostat and methionine.